STRUCTURE AND COMPOSITION OF TREES IN THE GIRIMANIK NATURAL FOREST AREA, WONOGIRI, CENTRAL JAVA - Mandarasy, Mumtaza; Santhyami, Santhyami (Forestry Study Program University Of Mataram, 2025)
A tree is a woody plant with a main trunk and branches that grow upwards. Trees play an ecological role as carbon reserves and habitats for various fauna. This research is important to provide references related to tree diversity and natural forest ecosystems as a basis for policy-making to support ecosystem sustainability. Research on tree vegetation has never been conducted in the Girimanik Wonogiri Natural Forest Area, therefore, this study aims to observe the structure and composition of trees in this area. Data was collected using the one-hectare plot method, with 25 plots each measuring 20 x 20 cm. To meet the plot criteria for vegetation analysis, plot placement was carried out using the purposive sampling method. The results of this study show that the Girimanik Natural Forest Area has 40 species from 24 families, with the tree species having the highest importance value index are Quercus lineata and Ficus padana. The plant with the largest diameter is Trema orientalis. Natural forests have the highest tree diversity compared to artificial forests or agroforestry systems.